Neurotoxicity of intraneural injection of bupivacaine liposome injectable suspension versus bupivacaine hydrochloride in a porcine model. (March 2019) - Damjanovska, Marija; Cvetko, Erika; Kuroda, Maxine M.; Seliskar, Alenka; Plavec, Tanja; Mis, Katarina; Podbregar, Matej; Pintaric, Tatjana Stopar
Abstract: Objective: To test whether neurotoxic effects of a bupivacaine liposome injectable suspension differ from those of a standard formulation of bupivacaine hydrochloride (HCl) after intraneural injection into the sciatic nerves in pigs. Study design: Prospective, randomized study. Animals: Fifteen pigs, hybrids of Landrace and Large White. Methods: After the National Ethics Committee approval, 15 pigs were randomly allocated to three groups ( n  = 5/group) to receive intraneural injections of 4 mL of 1.33% bupivacaine liposome injectable suspension, 0.5% bupivacaine HCl or normal saline. Serial neurologic examinations were conducted to detect sensory and motor response to noxious stimuli using a modified Thalhammer's scale at 2 hour intervals for the first 12 hours after injection and daily thereafter for 2 weeks. Fiber characteristics (density) of the harvested sciatic nerves were measured during histomorphometric analysis. Inflammatory response was studied using immunohistochemical analysis. Data were tested using analyses of variance; p values for paired comparisons were Bonferroni adjusted. Results: Compared with bupivacaine HCl, bupivacaine liposome injectable suspension provided longer sensory (11.2 ± 1.8 hours versus 3.2 ± 1.1 hours, respectively, p < 0.0001) and motor (10.0 ± 2.0 hours versus 4.0 ± 1.4 hours respectively, p < 0.0001) blockade. Histomorphometric parameters were similar among the groups. No changes in axonal density or myelin structure indicative of injury to the sciatic nerves were observed in any of the groups. Number of immunopositive cells did not differ between the bupivacaine liposome injectable suspension (23 ± 6 cells per mm 2 ) and the bupivacaine HCl groups (21 ± 4 cells per mm 2 ), p > 0.90. Conclusions and clinical relevance: Intraneural injections of bupivacaine liposome injectable suspension or bupivacaine HCl in our porcine model did not result in evidence of neurotoxicity.